Antibiotic susceptibility of bacterial isolates from 502 dogs with respiratory signs. (4th April 2015) - Rheinwald, M.; Hartmann, K.; Hähner, M.; Wolf, G.; Straubinger, R. K.; Schulz, B.
Abstract : The aim of this study was to investigate the prevalence of bacterial species isolated from bronchoalveolar lavage fluid (BALF) samples taken from dogs with respiratory signs and to determine their antibiotic susceptibility. Clinical cases were included in the study if they showed signs of respiratory disease and data relating to bacterial culture and susceptibility of BALF samples were available. The medical records of 493 privately owned dogs that were presented between January 1989 and December 2011 were evaluated retrospectively. In 35 per cent of samples, no bacteria were cultured. Bacteria isolated from culture‐positive samples included Streptococcus species (31 per cent of positive cultures), Enterobacteriaceae (30 per cent, including Escherichia coli (15 per cent)), Staphylococcus species (19 per cent), Pasteurella species (16 per cent) and Pseudomonas species (14 per cent). Bordetella bronchiseptica as a primary respiratory pathogen was isolated in 8 per cent of cases. Enrofloxacin showed the best susceptibility pattern; 86 per cent of all isolates and 87 per cent of Gram‐negative bacteria were susceptible to this antibiotic. Amoxicillin/clavulanic acid yielded the best susceptibility pattern in Gram‐positive bacteria (92 per cent). Therefore, these antibiotics can be recommended for empirical or first‐line treatment in dogs with bacterial lower respiratory tract infections.